The in vivo and in vitro approaches for establishing a link between advanced glycation end products and lung cancer. Issue 11 (4th August 2018) - Khan, Hamda; Khan, Mohd. Sajid; Ahmad, Saheem
Abstract: Advanced glycation end products (AGEs) are directly related to third aging‐associated diseases, such as cardiovascular diseases, arteriosclerosis, and neurodegeneration. Likewise, these irreversible and nonenzymatic products have been reported to be involved in the progression of malignant cancers. In general, aging‐associated diseases and the initiation of cancer have been subjects of interest for several years. Few studies on the role of AGEs in cancer have been performed on cell lines. Moreover, past investigations in the field of glycation biology still lack the knowledge of in vivo and in vitro approaches for cancer cells. Accordingly, we aimed to focus on and establish a link between cancer and glycation with respect to all the possible AGEs. In our study, the levels of carboxymethyllysine (CML) increased by 50.94% in an animal model of glycation, whereas in an animal model of cancer, the contents of CML increased by 45.94% compared with their negative controls. Similarly, fluorescent AGEs were also examined and were found to be increased by 65.3% and 58.63% in the animal models of glycation and cancer, respectively, compared with the control subjects. The protein carbonyl contents were also found to be enhanced in the animal models of glycation and cancer. In our study, the levels of reactive oxygen species were also found to be significantly increased in the in vitro model of cancer cells as compared with the controls. Such an initial breakthrough indicated that AGEs were present in the serum of the animal models of cancer and glycation. Abstract : The glycation model system can represent an attractive model system for the treatment and cure of advanced glycation end products (AGEs)‐related complications. A successful correlation between fluorescent/nonfluorescent AGEs and lung cancers was observed.